Process Evaluation: Standard, Effectiveness, Efficiency and Sustainability of Maternity Nursing Care - Laili Rahayuwati; Ermiati E; Mira Trisyani (Jurnal Keperawatan Padjadjaran, 2016)
Although globally there is a change in the trend of epidemiology from infectious diseases to chronic diseases, the prevalence and incidence of infectious diseases as well as MMR (Maternal Mortality Rate) and IMR (infant mortality rate) in Indonesia is still high. In year 2000, Faculty of Nursing of the Universitas Padjadjaran in collaboration with Hasan Sadikin Hospital built a model of treatment room, which was affiliated with obstetric gynecology room for improving integrated quality of health care services and education. The model built in this room aimed to : 1) Improve the quality of health care service; 2) to develop the student’s experiences with patients; 3) Provide quality nurse education to support students; 4) encourage students to improve the results of clinical prctice. The objective of process evaluation in this study was to give an insight to an appropriate model for maternity nursing service. This results showed on the one hand , there are some records not yet achieved an ideal standard , lack of effectiveness and efficiency of care delivery, namely: 1 ) the ratio of midwives and patients are not ideal ; 2 ) No one consultant obstetrician gynecologist and one doctor for every room . As well as challenges to sustainability care that meets the standards of maternity care. Conclusion: this study recommends to take a comprehensive strategic planning for improving nursing and midwifery services that involve all relevant stakeholders in the government, civil society, service delivery, education, and professional organizations.Keywords:Effectiveness, efficiency, evaluation, maternity nursing care, standard.Proses Evaluasi: Standar, Efektifitas, Efisiensi, dan Keberlangsungan Pelayanan Keperawatan MaternitasAbstrakMeskipun secara global ada perubahan dalam tren epidemiologi dari penyakit menular ke penyakit kronis, prevalensi dan insiden penyakit menular serta MMR (Angka Kematian Ibu) dan AKB (angka kematian bayi) di Indonesia masih tinggi. Tahun 2000, Fakultas Keperawatan Unpad bekerja sama dengan Rumah Sakit Hasan Sadikin, Bandung membangun sebuah model dari ruang perawatan, yang berafiliasi dengan ruang obstetrik ginekologi. Model yang dibangun tersebut bertujuan untuk; 1) meningkatkan kualitas pelayanan kesehatan; 2) pengembangan pengalaman mahasiswa dengan pasien; 3) penyediaan pendidik perawat yang berkualitas untuk mendukung mahasiswa; 4) mendorong mahasiswa untuk meningkatkan hasil praktek klinis. Tujuan dari penelitian ini adalah memberikan informasi dan evaluasi tentang standar, efektifitas, efisiensi, dan keberlangsungan (sustainaibility) pelayanan keperawatan maternitas. Hasil penelitian menunjukkan: di satu sisi, ada beberapa catatan tidak belum tercapainya standar ideal, kurang efektivitas dan efisiensi perawatan persalinan, yaitu: 1) rasio bidan dan pasien tidak ideal; 2) ada satu konsultan ginekolog obstetri dan satu dokter untuk setiap kamar. Serta tantangan terhadap keberlangsungan asuhan perawatan maternitas yang memenuhi standar. Kesimpulan: Penelitian ini merekomendasikan untuk mengambil perencanaan strategis yang komprehensif untuk meningkatkan pelayanan keperawatan dan kebidanan yang melibatkan semua pihak terkait di pemerintah, masyarakat sipil, pelayanan, pendidikan, dan organisasi profesiKata kunci:Asuhan keperawatan maternitas, efektifitas, efisiensi, evaluasi, standar